Internalisasi Nilai Akhlak Islam dalam Etika Interaksi Digital Guru dan Peserta Didik: Sebuah Kajian Literatur - Tyas Ayu Farah Dina; M. Fahmy Fredyansyah Maulana; Azzakiya Aufa Shalina; Nur Khasanah (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2026)
The transformation of digital-based learning has changed the pattern of interaction between teachers and students from face-to-face communication to technology-mediated communication. This transformation has introduced various ethical challenges, including declining communication politeness, the spread of unverified information, and a lack of responsibility in the use of digital media. This study aims to formulate a conceptual framework for the internalization of Islamic moral values as a foundation for ethical digital interactions between teachers and students from the perspective of Islamic Religious Education. The study employed a qualitative approach using a library research method. Data were obtained from secondary sources, including books, scholarly journal articles, conference proceedings, and academic documents relevant to digital ethics, learning interactions, and Islamic moral values. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, which consists of data condensation, data display, and conclusion drawing, and was further strengthened through content analysis to identify patterns and relationships among concepts. The findings indicate that the values of adab (proper conduct), amanah (trustworthiness), and tabayyun (verification) serve as the primary foundations of ethical digital interaction in education. The internalization of these values takes place through the stages of value transformation, value transaction, and transinternalization, supported by teachers’ roles as role models, facilitators, mentors, and motivators. This study proposes a conceptual framework for the internalization of Islamic moral values that can serve as a basis for strengthening digital ethics in Islamic Religious Education learning in the digital era.